Advancement trajectory of emerging landsenses ecology for sustainability research and implementation. Issue 7 (3rd October 2022) - Zhang, Lan; Huang, Guowen; Li, Yongtao; Bao, Shitai
ABSTRACT: To objectively identify the research hot topics, development trends, and frontiers of landsenses ecology, the current paper uses CiteSpace software to carry out keyword co-occurrence and cluster analysis on relevant literature collected from the Web of Science database. The paper then summarizes characteristics and trends in the development of this discipline and briefly introduces linguistic landsense ecology, a branch of landsenses ecology concerned with the study of the relationship between language and environment. This survey shows that landsenses ecology draws on the Chinese philosophy of integrating 'heaven, earth and man', and emphasizes the comprehensive analysis of various elements both natural, economic, and humanistic, as well as incorporating multidimensional sensitivity to people's physical senses and psychological perceptions. Its goal is to realize a dynamic balance between human well-being and ecosystem services and to achieve their sustainable development. In general, landsenses ecology provides the advantages of an analytical framework for sustainable development oriented towards human well-being, and great progress has been made in obtaining in-situ information on ecosystem services via the quantification of human perceptions. This integrated approach promotes an organic combination of natural environmental factors with human physical senses and psychological perceptions, so as to provide comprehensive and dynamic information for the sustainability of ecosystems in relation to human well-being. Landsenses ecology also has unique cross-cultural and interdisciplinary features, providing a theoretical framework for researchers from different cultural and disciplinary backgrounds in dealing with complex socio-environmental problems, and thus ensuring the orderly implementation of sustainable development.